Keterlibatan Notaris Dalam Pemberantasan Money Laundering Berdasarkan PP No. 43 Tahun 2015 Dikaitkan Dengan Asas Kerahasiaan Terbatas - Aganita Dhaneswara (Lex Renaissance, 2020)
In carrying out their duties and offices, a notary must always be guided by the Law on Public Notary (UUJN). In the UUJN, notaries are obliged to keep confidential everything concerning the deed they have produced and all information obtained for formulating the deed in accordance with the oath of office, unless the law stipulates otherwise. The obligation of notaries to report suspicious transactions is stated in Government Regulation (PP) No. 43 of 2015 on Reporting Parties in the Prevention and Eradication of Money Laundering, instead of by legislationg. Hence, this study intends to examine: first, whether the mention of a notary in the PP does not violate the principle of limited confidentiality; and second, whether the mention of a notary in the PP does not harm the notary. This is a normative legal research with qualitative descriptive analysis. The results of the study concluded that the obligation of notaries to report suspicious transactions caused debate among notaries and the Financial Transaction Reports and Analysis Center (PPATK). In theory, this obligation violates the principle of limited confidentiality, but if it is seen in the Money Laundering Law, the provisions of confidentiality can be excluded. This obligation does not cause harm to the notary because the notary as a witness and the reporting party is given protection by the state as regulated in the Money Laundering Law.